STUDENTS’ ATTITUDE AND TECHNOLOGICAL ACCEPTANCE TOWARDS ONLINE ENGLISH LEARNING CLASS - Ami Girsang (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of information technology and changes in the education system following the COVID-19 pandemic have led to the widespread transition of English language learning to online learning at Indonesian universities. While online learning offers flexible access to learning materials, its implementation also presents various challenges, such as limited interaction, speaking anxiety in virtual classes, reduced learning motivation, and difficulty understanding materials. Based on Moore's (1972) Transactional Distance Theory, these conditions are expected to result in negative student attitudes toward online learning. However, preliminary findings indicate that approximately 70% of English Literature students at Medan State University (UNIMED) showed positive attitudes toward online English learning, presenting an intriguing discrepancy between theory and practice. This study aims to describe students' attitudes toward online English learning through affective, behavioral, and cognitive dimensions based on Myers' (1996) ABC Theory of Attitude, and to identify factors influencing technology acceptance based on Davis's (1989) Technology Acceptance Model (TAM). A descriptive qualitative approach was used, supported by simple quantitative data. Twenty students completed questionnaires and seven participated in semi-structured interviews via WhatsApp. Results showed that students generally demonstrated positive attitudes across all three components. Affectively, most students felt comfortable and enjoyed the flexibility of online learning, although speaking anxiety remained present. Behaviorally, students actively attended classes, used digital tools, and engaged in independent learning. Cognitively, students recognized the usefulness of online platforms and content relevance, though they remained skeptical about its equivalence to face-to-face instruction. TAM analysis revealed that perceived usefulness and perceived ease of use were key drivers of technology acceptance. It is concluded that positive attitudes are sustained when technology is accessible, instructors are supportive, and students possess sufficient digital literacy